Adoption of serious games by teachers: the analysis method of structure, interface and use - Farida Bouroumane; Abderrahim Saaidi; Mustapha Abarkan (Institute of Advanced Engineering and Science, 2022)
In this article, we determine how to facilitate the analysis of serious games so that teachers could effectively integrate them in their teaching. The aim is to identify the mechanisms that would make serious games exploitation useful. We propose a method for the analysis of serious games that is based on the separation of their components along three phases. In addition, we set up a platform based on a data analysis process that is composed of six steps that help to set the basis of a verification procedure that targets the content of a game and thus facilitates the work of teachers through effective implementation of serious games as teaching strategies (TIC). The obtained experimental results show that 82.5% of the study participants expressed that the use of the platform has helped them to change their perspective on the need to use serious games as an educational tool.